2018
DOI: 10.1007/s12020-018-1607-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for central neck lymph node metastases in follicular variant vs. classic papillary thyroid carcinoma

Abstract: No differences were observed between cPTC and fvPTC with regard to risk factors of CNM. fvPTC seems associated with a lower incidence of CNM, presumably because of the higher rate of incidental diagnosis. With the exception of age, in patients with a preoperative diagnosis of PTC, no preoperatively available clinical parameter is a reliable predictor of CNM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In distant metastases of various types of cancer, the interaction of platelets and tumor cells that is fostered by T4 may contribute to metastasis formation ( 37 ). It is not clear what the factors are that lead to local—particularly, central—lymph node metastases from differentiated thyroid cancers ( 51 ). We propose that local T4 production by thyroid cancer cells may be a factor that contributes to local, as well as distant, metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In distant metastases of various types of cancer, the interaction of platelets and tumor cells that is fostered by T4 may contribute to metastasis formation ( 37 ). It is not clear what the factors are that lead to local—particularly, central—lymph node metastases from differentiated thyroid cancers ( 51 ). We propose that local T4 production by thyroid cancer cells may be a factor that contributes to local, as well as distant, metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the difference are currently unknown. Interestingly, several studies have showed that compared with the classic variant, follicular variant of PTC is protective for lymph node metastasis [36,37]. The low expression of IL-18 in follicular variant is just right consistent with the reduced incidence of nodal metastasis in this variant.…”
Section: Discussionmentioning
confidence: 84%
“…Despite an adequate preoperative study generally is able to identify clinical evidence of extrathyroidal extension and/ or multifocality and/or lateral neck lymph nodes involvement in PTC patients, the N stage of the central neck is quite hard to define both preoperatively and intraoperatively since occult central nodal metastases occurred in 40-80% of PTC patients [11,[14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…An accurate preoperative work up could led to identify some suspicious characteristics (e.g., macroscopic evidence of multifocality or extrathyroidal extension; evidence of lateral neck lymph node metastases) [11,14,15,17], but it is well known that it is hard to reliably define the central neck nodal status pre-and even intra-operatively [18][19][20].…”
Section: Introductionmentioning
confidence: 99%